Peran Aktor Multi-Stakeholder dalam Pemulihan Ekonomi Pariwisata Kota Semarang Tahun 2020-2021 - Andhika Joshua Loandy Limin; Wilson M. A. Therik; Triesanto Romulo Simanjuntak (Jurnal Social Science, 2023)
Tourism plays a crucial role in the economy of Semarang City. Tourism not only impacts the economic aspect but also influences the social life of the community. Based on statistical data, there has been a 24.48 percent decrease in tourist occupancy rates. Several supporting facilities and tourism businesses were also forced to temporarily close due to the COVID-19 pandemic. Multi-stakeholder actors collaborate in efforts to revive the tourism economy while still adhering to health protocols. This research aims to further examine the role of multi-stakeholder actors in the economic recovery of Semarang City's tourism sector. This study employs a qualitative research method with a descriptive type. The results of this study indicate that multi-stakeholder actors are focused on implementing health protocols in the tourism industry, assisting tourism businesses in obtaining CHSE certification, collaborating with academics in the development and optimization of tourism destination facilities and infrastructure, including changes in online reservations, the renovation of the Kota Lama, Lawang Sewu, Mandala Bhakti Museum dan Katedral.